Fluorescence Quenching of Graphene Quantum Dots by Chloride Ions: A Potential Optical Biosensor for Cystic Fibrosis - Ifrah, Zahid; Shah Rukh, Abbas; Muhammad Nauman, Sharif; Maryam, Shahid; Rahat, Ullah (Frontiers in Materials, 2022)
Cystic fibrosis is a genetic disorder caused by a mutation in the cystic fibrosis transmembrane conductance regulator (CFTR) gene that encodes an ABC transporter-class ion channel protein, resulting in sticky and thick mucus secretion which clogs the airways and leads to respiratory failure and other complications. It also results in higher chloride ions (Clˉ) in body fluids. Cystic fibrosis is generally detected using the sweat chloride test and ion exchange chromatography, which are lab restricted. Therefore, there is a dire need to develop portable assays to monitor circulatory changes (Clˉ ion detection) to detect CF at the point of care. In this work, fluorescence quenching of graphene quantum dots (GQDs) was used as a property of the optical sensor for chloride ion detection. GQDs were synthesized by varying the carbonizing temperature and time, and then their optical and fluorescence (FL) quenching was investigated upon exposure to chloride ions in comparison with different ionic species. GQDs synthesized at 160°C for 50 min were chosen as they displayed the highest fluorescence. The morphological and optical characterization confirmed the preparation of 12–15 nm GQDs, which were amorphous in nature with the peak emission observed at 462 nm when excited at 370 nm. The fluorescence quenching response of GQDs with Clˉ ions displayed linearity up to 100 mM with a correlation coefficient of 0.98 and the lowest detection limit of approximately 10 mM Clˉ ions.